2010
DOI: 10.1002/aic.12240
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen generation from noncatalytic hydrothermolysis of ammonia borane for vehicle applications

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Ammonia borane (AB) is a promising hydrogen storage material as it contains 19.6 wt % hydrogen. In this article, our recently developed hydrothermolysis approach to release hydrogen is studied over a wide range of AB concentrations (6-88 wt %), at pressure 14.7 and 200 psia, and temperature 85-135 C. It is shown that with increasing AB concentration up to 77 wt %, the H 2 yield increases, and that the role of thermolysis, when compared with hydrolysis, increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
32
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 35 publications
6
32
1
1
Order By: Relevance
“…Above 500°C, AB can be completely decomposed to form boron nitride (BN). The residue BN is not preferred for regeneration due to high chemical and thermal stability and hence ammonia borane is treated as a disposable source [7]. The main hurdle in hydrogen release is the slow kinetics at lower temperatures leading to long induction period [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Above 500°C, AB can be completely decomposed to form boron nitride (BN). The residue BN is not preferred for regeneration due to high chemical and thermal stability and hence ammonia borane is treated as a disposable source [7]. The main hurdle in hydrogen release is the slow kinetics at lower temperatures leading to long induction period [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of NH 3 was released and the wt % of AB, the pressure, and the heating rate had substantial influences on NH 3 liberation. [70] For example, an increase of the NH 3 content from 6 to 9.9 mol % was observed when AB was increased from 40 to 50 wt %, whereas a further increase in the AB content resulted in a decreased NH 3 content. This was rationalized by considering NH 3 as one of the products of hydrolysis; hence, its formation is more favorable when the H 2 O content is high.…”
Section: Nh 3 Releasementioning
confidence: 95%
“…One of the drawbacks associated with the hydrolysis of AB is the generation of NH 3 , [24,59,69,70] which is detrimental for fuel cell applications. For example, Demirci and co-workers have reported that the characteristic pungent odor of NH 3 (average odor threshold of 35 mg m À3 or ca.…”
Section: Nh 3 Releasementioning
confidence: 99%
“…368 Recently, novel highly asymmetric YSZ hollow fibers were prepared via a combined phase inversion and sintering method. 369 As shown by Kanakwa et al, 370 these YSZ hollow fibers have the potential to provide an attractive structure for nickel/yttria-stabilized zirconia/lanthanum strontium manganite (Ni/YSZ/LSM) electrolyte-supported microtubular SOFCs, because of the reduced thickness of the gas-tight dense electrolyte layer and increased inner surface area, while maintaining good mechanical properties.…”
mentioning
confidence: 97%